Untangling hope labour from care labour: LGBT+ people navigating equality, diversity and inclusion work in higher education. - Slater, Tig; Simms, Drew; Formby, Eleanor (Journal of Gender Studies, 2026)
This article reports on the 'Whose Rainbow?' project, exploring LGBT+ staff and students' conflicted relationships to Equality, Diversity and Inclusion (EDI) work in UK Higher Education (HE). Drawing on interview data, we illustrate the expectation on LGBT+ people to 'embody diversity' within HE, and the labour that comes with such expectation. Whilst most participants undertook some EDI work, they were aware of their own potential exploitation, and the limits of the work itself. Yet, participants felt a responsibility to make change for other LGBT+ people, particularly those with less institutional power. We theorize this conflict through the concepts of hope labour and care labour. Whilst hope labour is usually used to think about (exploitative) voluntary work done in the hope of secure(r) employment, we argue that it can be productively used to think about marginalized people's relationships to EDI work. We conceptualize care labour, however, as a more radical act involving collective efforts to redistribute power. We show that whilst most participants were striving towards care labour, this was hard to disentangle from institutionally demanded hope labour. Nevertheless, we highlight glimmers of care: through trade unions, informal networks, acts of defacement and radical reimaginings of universities.